(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article, which presents a theoretical study, proposes a reflection on the urgency of reconfiguring human relations based on the principles of fraternity and solidarity, using Edgar Morin’s complex thought as a reference. In a context of civilizational crisis, marked by fragmentation, inequalities, and threats to the common future of humanity, the author invites us to build an open fraternity that recognizes the other in their alterity and promotes ethical coexistence in diversity. Fraternity has biological and cultural roots and should be understood as a profound expression of the human condition, present in dynamics of cooperation, mutualism, and interdependence. The construction of a planetary fraternity requires overcoming the limits of closed identities and cultivating "oases of hope," that is, spaces of ethical and social resistance that promote solidarity and sustainable practices, such as mutual aid networks, solidarity economy, and community actions. Solidarity is not limited to punctual altruism but constitutes a structuring principle of collective and planetary life. Rooted in the awareness of a shared belonging to the human species and to the Earth, an ethic is needed that is capable of overcoming individualism and promoting responsible, democratic, and regenerative coexistence. Thus, the article concludes that the fraternal and solidarity-based paths proposed by Morin are central to the construction of a new civilizational paradigm, capable of facing global challenges with hope, awareness, and shared responsibility.